Comparison of data on deaths by Covid-19 between three sources of information, Maranhão (Research, Society and Development, 2020)
The work aimed to compare the death data by Covid-19 in Maranhão using three sources of information. To this end, we carried out a cross-sectional and descriptive study on death data by Covid-19 in Maranhão, from April 7 to May 15, 2020. Data from the State Department of Health (SES / MA), Panel Covid -19, from the Ministry of Health, and the Civil Registry Information Center (CRC Nacional), analyzed according to sex and age group. 550 deaths were reported by SES / MA, 494 on the Covid-19 Panel and 281 on the National CRC. More deaths are observed in males and in the age group above 60 years. The delay in the recording of deaths and errors in monitoring, coupled with the great underreporting of the real numbers of deaths, require improvements in order to be able to portray it closer to the real scenario.